Chromotropic acid-formaldehyde reaction in strongly acidic media. The role of dissolved oxygen and replacement of concentrated sulphuric acid - Fagnani, E.; Melios, C. B.; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier B.V., 2003)
The procedure for formaldehyde analysis recommended by the National Institute for Occupational Safety and Health (NIOSH) is the Chromotropic acid spectrophotometric method, which is the one that uses concentrated sulphuric acid. In the present study the oxidation step associated with the aforementioned method for formaldehyde determination was investigated. Experimental evidence has been obtained indicating that when concentrated H2SO4 (18 mol l(-1)) is used (as in the NIOSH procedure) that acid is the oxidizing agent. on the other hand, oxidation through dissolved oxygen takes place when concentrated H2SO4 is replaced by concentrated hydrochloric (12 mol l(-1)) and phosphoric (14.7 mol l(-1)) acids as well as by diluted H2SO4 (9.4 mol l(-1)). Based on investigations concerning the oxidation step, a modified procedure was devised, in which the use of the potentially hazardous and corrosive concentrated H2SO4 was eliminated and advantageously replaced by a less harmful mixture of HCl and H2O2. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: formaldehyde; chromotropic acid; spectrophotometry; dissolved oxygen